Clinical outcomes of three follitropin alfa preparations for ovarian stimulation using an oral micronized progesterone-primed protocol in an oocyte donation program - Cruz, María; Howles, Colin M. (Frontiers in Endocrinology, 2024)
This large multicenter study aimed to evaluate clinical outcomes using three follitropin alfa preparations within a progestin-primed ovarian stimulation (PPOS) protocol, while identifying contributing factors to cycle success. A retrospective, anonymized cohort analysis was conducted on donor-recipient cycles from 12 clinics during 2019 to 2021. A total of 7389 oocyte donors underwent ovarian stimulation (OS) with three follitropin alfa preparations (Ovaleap® [n=3231], Bemfola®[n=3542], Gonal-F® [n=616]) were included. Stimulation began on cycle days 2 or 3 with daily administration of 150-225 IU follitropin alfa. Additionally, 10 mg medroxyprogesterone acetate (MPA) was administered daily until GnRH agonist trigger using a single dose of 0.2mg GnRH agonist for final follicular maturation. Statistical analysis included ANOVA, Chi-squared, and logistic regression. While there were some differences in patient and stimulation characteristics, including donor age and the number of retrieved oocytes, the clinical variables did not significantly differ among the three study groups. Linear regression revealed donor age [0.986 (0.974-0.999)] and number of mature oocytes [1.027 (1.007-1.047)] significantly impacted ongoing pregnancy rates, while the type of follitropin alfa [1.048 (0.956-1.149)] used did not. No significant differences were observed in the cumulative live birth rate (CLBR) among oocytes obtained from stimulation with Bemfola® (64.9%), Gonal-F® (64.1%) and Ovaleap® (66.1%), p= 0.385. This study demonstrated comparable clinical outcomes and CLBR between biosimilars and the reference product of follitropin alfa within PPOS protocols, indicating that they are interchangeable in a real-world patient setting.